How Taiwanese parents of children with autism spectrum disorder experience the process of obtaining a diagnosis: A descriptive phenomenological analysis. (May 2018) - Chao, Kuo-Yu; Chang, Hsueh-Ling; Chin, Wei-Chih; Li, Hsin-Mei; Chen, Sue-Hsien
An autism spectrum disorder can result in considerable stress and confusion for parents as they attempt to understand their child's problems and obtain a diagnosis. Few studies have explored the parental experience in the context of Chinese culture. The purpose of this study was to understand the experiences of parents in Taiwan of children diagnosed with autism spectrum disorder. In total, 15 parents, 1 father and 14 mothers, were recruited by purposive sampling. This qualitative study used semi-structured interviews and descriptive phenomenological analysis. The findings indicated that parents of children diagnosed with autism spectrum disorder underwent five coping experiences during the diagnostic process: (1) uncertainty and difficulty understanding their child's behaviour, which occurred during the pre-diagnosis phase; (2) obligation to obtain professional services; (3) anxious searching for a second opinion, which occurred during the diagnosis phase; (4) acceptance and fortitude and (5) further adjustment during the post-diagnosis phase. Our findings add to our understanding of how parents experience the diagnostic process, which could improve medical professionals' counselling and support for parents at the stage of obtaining a diagnosis for their children.